Environmental friendly exploration of cinnamon bark (Cinnamomum verum) based yellow natural dye for green coloration of bio‐mordanted wool fabric. Issue 3 (30th December 2021) - Adeel, Shahid; Habib, Noman; Batool, Fatima; Amin, Nimra; Ahmad, Tanvir; Arif, Saba; Hussaan, Muhammad
Abstract: In the era of the industrial revolution with the increased demand for sustainable products, the use of natural products particularly herbal‐based bio‐colorants in every walk of life is increasing. In the current study, cinnamon as a source of natural dye for wool has been explored under the influence of microwave radiations and the application of sustainable bio‐mordants has been done under mild conditions. Microwave radiations for 1–6 min have been used to increase the extraction yield and 1–10 g/100 ml of sustainable chemical and bio‐mordants have been employed to get excellent color characteristics. The utilization of reduced amounts of herbal nature‐based bio‐mordants in comparison with chemical anchors after microwave irradiation of extract and the woolen fabric has not only produced new shades but also improved the color characteristics from good to excellent. It is concluded that the use of microwave treatment as the sustainable tool has excellent potential to isolate the colorant from cinnamon bark under mild conditions; whereas the addition of bio‐mordants has valorized the coloring process greener and more valuable.